2'5' oligoadenylate synthetase, an interferon induced enzyme: direct assay methods for the products, 2'5' oligoadenylates and 2'5' co-oligonucleotides. - Justesen, J (1980)
The interferon induced enzyme 2'5' oligoadenylate synthetase produces 2'5' pppA(pA)n the first discovered natural nucleotide with a 2'5' linkage. We describe a direct assay of this enzyme based on separation by thin layer chromatography (TLC) of the substrate ATP and the products 2'5' pppA(pA)n (n larger than or equal to 1). This technique presents obvious advantages compared to the currently used methods. Moreover the enzyme uses other nucleotides as substrates forming co-oligonucleotides 2'5 pppA(pA)n pN (N = U,G,C,dA,dG,dT and dC). Additional procedures are described using different developing solvent systems for the separation of the core-2'5' oligonucleotides (2'5' A(pA)npN) containing AMP-residues entirely and those with another nucleotide at the 2' end.